(untitled) (GESTIÓN Y TENDENCIAS, 2021)
The COVID-19 pandemic has forced companies and institutions to innovate in order to confront the economic and social changes it produced. This phenomenon has accelerated processes that will affect society, especially in business and institutional development. Within this framework, this Special Issue of Gestión y Tendencias presents two cases of innovation developed during the pandemic and two analyses that invite reflection on how to approach the new normal. We conclude with a reflection on the need to innovate by combining the organizational dimension with the innovation ecosystem.